2011
DOI: 10.1021/nn203160n
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nanocrystalline Semiconducting Graphene Monoxide during Thermal Reduction of Graphene Oxide in Vacuum

Abstract: As silicon-based electronics are reaching the nanosize limits of the semiconductor roadmap, carbon-based nanoelectronics has become a rapidly growing field, with great interest in tuning the properties of carbon-based materials. Chemical functionalization is a proposed route, but syntheses of graphene oxide (G-O) produce disordered, nonstoichiometric materials with poor electronic properties. We report synthesis of an ordered, stoichiometric, solid-state carbon oxide that has never been observed in nature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
94
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 30 publications
(52 reference statements)
13
94
0
Order By: Relevance
“…As the typical values of x in CO x in the current experiments are usually smaller than 0.5, we can understand that inhomogeneous phase generally exists in almost all the GO samples. Our calculations explain quite well the recent experimental discovery that thermally reduced GO is separated into unoxidized graphene regions and high-oxidized GO regions that have a quasi-hexagonal unit cell with an unusually high 1:1 O:C ratio [20].…”
supporting
confidence: 84%
See 3 more Smart Citations
“…As the typical values of x in CO x in the current experiments are usually smaller than 0.5, we can understand that inhomogeneous phase generally exists in almost all the GO samples. Our calculations explain quite well the recent experimental discovery that thermally reduced GO is separated into unoxidized graphene regions and high-oxidized GO regions that have a quasi-hexagonal unit cell with an unusually high 1:1 O:C ratio [20].…”
supporting
confidence: 84%
“…We find that the miscibility temperature of GO even at quite low oxygen concentration (x ≤ 0.05) is around 4000 K, which is rather high and close to the melting point of graphite [31]. The calculated phase diagram clearly demonstrates that it is impossible to get homogeneous GOs by the conventional Hummers methods under the typical temperature for preparing thermally reduced GOs [6,8,9,15,20,21].…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…A recent study showed graphene monoxide production having a band gap of ~0.9 eV with a thermal reduction (~500-700°C) of GO in vacuum. Intercalated water in GO demonstrated an unobserved atomic structure and morphology, which is a phase segregation resulting in graphitic regions with little or no oxidation after annealing (Mattson et al, 2011). It was also found that water molecules from the ambient or at the SiO 2 /graphene interface can split into H + and OH -with further attaching to graphene and generating a band gap (Echtermeyer et al, 2008).…”
Section: Selected Techniques For Rgo Production and Exfoliation Procementioning
confidence: 98%